2007
DOI: 10.1111/j.1460-9568.2007.05660.x
|View full text |Cite
|
Sign up to set email alerts
|

mGluR7 inhibits glutamate release through a PKC‐independent decrease in the activity of P/Q‐type Ca2+ channels and by diminishing cAMP in hippocampal nerve terminals

Abstract: The modulation of calcium channels by metabotropic glutamate receptors (mGluRs) is a key event in the fine-tuning of neurotransmitter release. Here we report that, in hippocampal nerve terminals from adult rats, the inhibition of glutamate release by the group III mGluR agonist L-2-amino-4-phosphonobutyrate (L-AP4) is largely mediated by mGluR7. In this preparation, P/Q-type Ca(2+) channels support the major component of glutamate release while the remaining release is supported by N-type Ca(2+) channels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 58 publications
(107 reference statements)
1
36
0
Order By: Relevance
“…Thus, agonist activity of this compound at mGluR7 could depend on the G proteins or second messenger systems that are activated in a particular cell type or on other cell or pathway-specific factors. Previous studies have led to the suggestion that activation of mGluR7 leads to inhibition of P/ Q-type calcium channel activity in hippocampal nerve terminals by βγ subunits (Martin et al, 2007;Perroy et al, 2000). Since activation of GIRK channels also occurs through activation of βγ subunits (Saugstad et al, 1996), it is interesting that we observed a correlation between the lack of effect of AMN082 in a cell-based system that relies upon βγ-mediated signaling after mGluR7 activation and synaptic transmission.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, agonist activity of this compound at mGluR7 could depend on the G proteins or second messenger systems that are activated in a particular cell type or on other cell or pathway-specific factors. Previous studies have led to the suggestion that activation of mGluR7 leads to inhibition of P/ Q-type calcium channel activity in hippocampal nerve terminals by βγ subunits (Martin et al, 2007;Perroy et al, 2000). Since activation of GIRK channels also occurs through activation of βγ subunits (Saugstad et al, 1996), it is interesting that we observed a correlation between the lack of effect of AMN082 in a cell-based system that relies upon βγ-mediated signaling after mGluR7 activation and synaptic transmission.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, the dependency of release on [Ca 2+ ] o seems to be an intrinsic property of the channel, probably related to the distance of N‐type channels from release sites, as revealed by the greater sensitivity of N‐type channel‐mediated release to Ca 2+ chelators (Wu et al. , 1999; Martín et al. , 2007).…”
Section: Resultsmentioning
confidence: 99%
“…5). Compensatory mechanisms, if present, would not necessarily restore physiological synaptic transmission, as P/Q- and N-type channels have contrasting functional properties that might translate to different roles in transmitter release (Zhang et al, 1996; Wu et al, 1999; Martín et al, 2007; Zaitsev et al, 2007). In contrast to the decreased inhibitory connectivity (Faria and Prince, 2010; Jin et al 2011) and N-channel density (Fig.…”
Section: Discussionmentioning
confidence: 99%